An Oddi tumor case treated by endoscopic papillectomy - , Fatih HİLMİOĞLU and , Murat ALADAĞ and , Vildan TAŞKIN and , Melih KARINCAOĞLU and , Bülent MİZRAKİ and; lent YILDIRIM (Turkish Journal of Gastroenterology 1, 2019)
-